Peningkatan Mutu Pembelajaran Melalui Manajemen Kelas Partisipatif Guru Dan Siswa - Azizah, Mar'atul; Usman, Azizah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
The quality of education has become a central issue in Indonesia's education reform. One effort to improve the quality of learning is through the implementation of participatory class management. This study aims to describe the implementation of participatory class management at MA Ar-Rahman Sumoyono and its effect on improving the quality of learning. The study employs a qualitative approach with a case study design. The research subjects were 2 teachers and 6 students selected purposively. Data were collected through interviews, observations, and documentation studies. The data were analyzed inductively through data reduction, data display, conclusion drawing and verification. The results show that MA Ar-Rahman Sumoyono has implemented the concept of participatory class management by involving teachers and students in planning, implementing, and evaluating learning. Its application has proven to have a positive impact on increasing student motivation and learning outcomes, as well as the level of student satisfaction with learning services. Thus, participatory class management is significantly able to improve the quality of learning in the school.